2011
DOI: 10.1007/s11242-011-9762-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Gas Production Potential of Some Particularly Challenging Types of Oceanic Hydrate Deposits

Abstract: We use the TOUGH+HYDRATE code to assess the production potential of some particularly challenging hydrate deposits, i.e., deposits that are characterized by any combination of the following factors: absence of confining boundaries, high thermodynamic stability, low temperatures, low formation permeability. Using high-resolution grids, we show that a new horizontal well design using thermal stimulation coupled with mild depressurization yields production rates that appear modest and insufficient for commerciall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 23 publications
5
57
0
Order By: Relevance
“…Moridis et al [12] simulated the gas production from the Mount Elbert gas hydrate deposit by depressurization using both vertical and horizontal wells, and the results showed that the horizontal wells could increase the production rates by almost two orders of magnitude when comparing with the vertical wells. After that, Moridis et al [23] further compared the production behaviors of a single horizontal well design and a two-well design, and found that the gas production rate of the two-well configuration was much higher than that of the single-well design. Combining depressurization and warm brine stimulation methods, Feng et al [24] investigated the hydrate dissociation performance in the South China Sea in two horizontal wells.…”
Section: Introductionmentioning
confidence: 99%
“…Moridis et al [12] simulated the gas production from the Mount Elbert gas hydrate deposit by depressurization using both vertical and horizontal wells, and the results showed that the horizontal wells could increase the production rates by almost two orders of magnitude when comparing with the vertical wells. After that, Moridis et al [23] further compared the production behaviors of a single horizontal well design and a two-well design, and found that the gas production rate of the two-well configuration was much higher than that of the single-well design. Combining depressurization and warm brine stimulation methods, Feng et al [24] investigated the hydrate dissociation performance in the South China Sea in two horizontal wells.…”
Section: Introductionmentioning
confidence: 99%
“…For a well spacing of 90 m, and a well length of 1000 m, the average gas production rate is 1.80 × 10 6 ST· m 3 /day. Comparing with the commercially viable production rate (2.8 × 10 5 ST· m 3 /day) in the Gulf of Mexico [33], gas production in this work is favorable. Figure 9.…”
Section: Production Behaviors With the New Horizontal Well System In mentioning
confidence: 77%
“…Similarly, the Class 2 hydrate deposit consists of a HBL and an underlying zone of mobile water. The hydrate accumulation in the SCS is similar to the Class 3 deposit which involves only a HBL without underlying mobile fluid zones, and this kind of hydrate reservoir is regarded as "challenging" for gas production [24].…”
Section: Dissociation Methodsmentioning
confidence: 99%
“…Subsequently, Li et al [10] further indicated that the hydrate dissociation rate increased with the increase of salinity. Recently, Moridis et al [11] showed that the dual horizontal well system is better than the single horizontal well layout because of preferable heat transference. Much research in recent…”
Section: Introductionmentioning
confidence: 99%